Electronic Contribution to the energetics of helically-wrapped nanotubes - FERREIRA, MAURO (My University, 2006)
Motivated by evidence of helical wrapping of polymeric molecules around nanotubes, we calculate the electronic contribution to the energetics of linear charge distributions around a nanoscale cylindrical structure. This contribution alone leads to an angular dependence on the total energy, suggesting the occurrence of preferential wrapping directions. We argue that this contribution may play a role in determining the wrapping geometry of continuous linear charge distributions surrounding a nanotube.
PUBLISHED
Keywords: Physics